Submental Muscle Activity is Delayed and Shortened During Swallowing Following Stroke. Issue 9 (29th May 2015) - Kim, Hye‐Ri; Lee, Seung Ah; Kim, Keewon; Leigh, Ja‐Ho; Han, Tai Ryoon; Oh, Byung‐Mo
Abstract: Objective: To evaluate the activities of the submental muscles using surface electromyography (sEMG) in patients presenting with dysphagia secondary to middle cerebral artery (MCA) infarction, and to compare the results with those in healthy volunteers. Design: Retrospective study design. Setting: A dysphagia clinic at a tertiary care university hospital. Participants: Twenty‐one patients presenting with dysphagia after unilateral MCA infarction were recruited into the study within 2 months of stroke onset. To serve as a control group, 13 healthy volunteers were enrolled. Main Outcome Measures: The primary sEMG parameters were swallowing onset, pretrigger duration, swallowing duration, and swallowing amplitude. Swallowing functional outcome was evaluated using the Videofluoroscopic Dysphagia Scale and the American Speech‐Language‐Hearing Association National Outcome Measurement System. Results: Patients with MCA infarction demonstrated significantly delayed swallowing onset ( P < .001) and shorter swallowing duration ( P = .003) compared with the controls. Duration from the start of sEMG activity and actual laryngeal elevation also was delayed in the patient group ( P = .042). At a cut‐off point of 0.13 seconds for swallowing onset, sensitivity was 85.7% and specificity was 69.2%. For swallowing duration, sensitivity was 84.6% and specificity was 66.7% with 1.05 seconds as the cut‐off point. Conclusions: Patients with MCA infarction showed not only delayed swallowing onset and pretrigger duration, but also shorter duration of sEMG activity compared with those in healthy volunteers. Our results suggest that dysphagia after stroke might be further compromised by delayed laryngeal response especially after the start of suprahyoid muscle activity, which represents impaired laryngeal protection mechanism.